Adolescent Resilience: Promotive Factors That Inform Prevention. (5th August 2013) - Zimmerman, Marc A.; Stoddard, Sarah A.; Eisman, Andria B.; Caldwell, Cleopatra H.; Aiyer, Sophie M.; Miller, Alison
Abstract: Resilience theory provides a framework for studying and understanding how some youths overcome risk exposure and guides the development of interventions for prevention using a strengths‐based approach. In this article, we describe basic concepts of the theory, such as promotive factors, and distinguish assets and resources that help youths overcome the negative effects of risk exposure. We also present three models of resilience theory—compensatory, protective, and challenge—and review empirical research on three promotive factors—ethnic identity, social support, and prosocial involvement—that include individual, family, and community levels of analysis and have modifiable qualities for informing interventions. Finally, we present examples of how research findings from the three promotive factors can be translated into interventions to enhance youth development.